Breaking wheat-based monocropping system through scaling of diverse crops and varieties in the highlands of Ethiopia - Kemal, Seid Ahmed; Bishaw, Zewdie; Aynewa, Yetsedaw; Mekonnen, Kindu; Asfaw, Addisu; Alene, Temesgen; Ebrahim, Mohammed; Dubale, Workneh; Gebreyes, Million; Thorne, Peter; Seifu, Haimanot (2024)
Bread wheat is the third important food crop in the highlands of Ethiopia. Monocropping and rust disease epidemics remain challenges to increase bread wheat productivity and production. One of the strategies used in the AFRICA RISING (2012-2022) project was re-introducing high-yielding food and malt barley, durum wheat, and food legumes into the bread wheat-based cropping system through participatory variety selection (Phase I) and, community seed production and scaling (Phase-II)